Pulmonary artery wave reflection and right ventricular function after lung resection. (January 2023) - Glass, Adam; McCall, Philip; Arthur, Alex; Mangion, Kenneth; Shelley, Ben
Abstract: Background: Lung resection has been shown to impair right ventricular function. Although conventional measures of afterload do not change, surgical ligation of a pulmonary artery branch, as occurs during lobectomy, can create a unilateral proximal reflection site, increasing wave reflection (pulsatile component of afterload) and diverting blood flow through the contralateral pulmonary artery. We present a cardiovascular magnetic resonance imaging (MRI) observational cohort study of changes in wave reflection and right ventricular function after lung resection. Methods: Twenty-seven patients scheduled for open lobectomy for suspected lung cancer underwent cardiovascular MRI preoperatively, on postoperative Day 2, and at 2 months. Wave reflection was assessed in the left and right pulmonary arteries (operative and non-operative, as appropriate) by wave intensity analysis and calculation of wave reflection index. Pulmonary artery blood flow distribution was calculated as percentage of total blood flow travelling in the non-operative pulmonary artery. Right ventricular function was assessed by ejection fraction and strain analysis. Results: Operative pulmonary artery wave reflection increased from 4.3 (2.1–8.8) % preoperatively to 9.5 (4.9–14.9) % on postoperative Day 2 and 8.0 (2.3–11.7) % at 2 months ( P <0.001) with an associated redistribution of blood flow towards the nonoperative pulmonary artery (r>0.523; P <0.010). On postoperative Day 2, impaired right ventricular ejection fraction was associated with increased operative pulmonary artery wave reflection (r=–0.480; P =0.028) and pulmonary artery blood flow redistribution (r=–0.545; P =0.011). At 2 months, impaired right ventricular ejection fraction and right ventricular strain were associated with pulmonary artery blood flow redistribution (r=–0.634, P =0.002; r=0.540, P =0.017). Conclusions: Pulsatile afterload increased after lung resection. The unilateral increase in operative pulmonary artery wave reflection resulted in redistribution of blood flow through the nonoperative pulmonary artery and was associated with right ventricular dysfunction. Clinical trial registration: NCT01892800.